Multi-objective mathematical programming subject to box boundary constraints on system parameters - Khoder, H (Computational ecology and software, 2024)
Multi-objective mathematical programming subject to box constraints on system parameters is an important problem in the fields of computer-aided design and decision-making theory, when there is an apparent conflict between multiple preference criteria. In this work, mathematical programming methodology has been proposed using a modern algorithm to solve multi-objective mathematical problems. The proposed algorithm to perform the ranking and classification procedures for the set of alternative solutions with boundary constraints is based on the concepts of parametric multi-aspect modeling of flexible complex systems. Interactive software has been implemented in the .Net environment to aid the decision-maker to identify the preference criteria and constraints on the system parameters, and then to choose the best solution from the morphological set depending on the developed algorithm. In addition, an illustrative numerical example solved by the proposed algorithm is presented at the end of this work.